Desarrollo embriológico del centro de la cara (1959)
1. Twenty normal embryos and fetus were chose for macroscopic and microscopic examination to study the prenatal development of the central core of the face. Some details of this development are particularized and the others completed with anatomical description already made. 2. The embryological development of the center of the face is described in accordance with the latest motphological data and prior revision of the literature to include the formative stages of the upper lip, septum, palate and nose. 3. The author insists that the nasomedian process does not intervene in the formation of the upper lip; that in reality nothings is known about the function of Jacobson s organ, and that this organ does not enter into the formation of fisures, harelip or cleft palate types, due to its anatomical location. 4. The fact is discussed that so far nothing is known about the force which causes the palatine laminae, origin of the palate, to change from the vertical to the horizontal position.